Perfectionism and burnout in women professional golfers - Kang, K. D.; Hannon, J. C.; Harveson, A.; Lee, J. W.; Nam, J. J.; Han, D. H. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Perfectionism and burnout have been thought to affect performance in sports. The aim of current study was to analyze differences between members of the Korean Ladies Professional Association (KLPGA) and non-KLPGA golfers as they relate to perfectionism, burnout and commitment as well as analyze the relationship between the same psychological factors and golf score during a 3-day professional golf tournament.